Feasibility of Routine Assessment of Exercise Knowledge and Safety in Youth With Type 1 Diabetes. Issue 5 (October 2019) - Roberts, Alissa J.; Mitrovich, Connor; Yi-Frazier, Joyce P.; Taplin, Craig E.
Purpose: This pilot study assessed the feasibility and satisfaction of an electronic clinical tool to survey management of exercise in youth with type 1 diabetes (T1DM) for use in an outpatient diabetes clinic setting. Methods: Fifty youth with T1DM were recruited (ages, 10-18 years; mean ± SD, 14.8 ± 2.4) and 11 diabetes providers. Prior to a clinic visit and with an electronic tablet, participants completed the Type 1 Diabetes Report of Exercise Practices Survey, which included 9 primary exercise management guidelines. Responses were flagged if contrary to guidelines, and automated individualized reports with personalized evidence-based recommendations were produced for providers prior to seeing the patient. Postclinic assessment surveys were completed by patients and providers. Results: Out of the 9 guidelines, a mean of 4 ± 0.9 responses per patient were flagged as potentially unsafe. Ninety-one percent of providers took <10 minutes to review and discuss the report with their patients. Ninety-one percent of providers rated the tool as highly useful in facilitating patient education regarding exercise guidelines at that clinic visit. Fifty-six percent of youth rated the tool highly when asked whether its use altered their planned behavior around exercise. When participants were asked if such a tool should be used routinely in diabetes clinic, 64% of provider responses and 60% of patient responses were highly positive. Conclusions: This electronic tool identified deficits in exercise management in youth with T1DM and improved education in the clinic visit regarding exercise, and a majority felt it feasible and desirable to include in routine outpatient diabetes care.